Health Passport: A blockchain-based PHR-integrated self-sovereign identity system - George, Merlin; Chacko, Anu Mary (Frontiers in Blockchain, 2023)
During the COVID-19 pandemic, it was necessary to validate a person's health status along with their identity to permit travel. This was facilitated via paper-based certificates and centralised digital apps. Even after COVID, it is anticipated that such health status verifications will be required for travel and other purposes. As a result, there needs to be an additional credential, a ``Health Passport'', that establishes whether a person satisfies the health requirements for various purposes. Digital credentials so prepared should be trustable, unforgeable, and verifiable. The Health Passport should be designed to protect the end-users privacy and give people control over the data they use to confirm their credentials. This paper explores the requirements for a generalised Health Passport system and uses Agent-Oriented Modelling to design a blockchain-based Self-Sovereign Identity system integrated with Personal Health Record (PHR) to address this requirement. The paper demonstrates the feasibility of the solution by implementing a proof of concept on Hyperledger Indy and Aries, integrated with PHR - MediTrans. Credential issuance and verification time were calculated, and it was observed that the time overhead was minimal. This solution allows Users to verify their credentials with the Verifier without revealing any significant personal information. Our solution can be integrated into any PHR solution as the SSI solution is added as a plugin to the PHR accessible via mobile/web app.